2020
DOI: 10.17221/218/2020-pse
|View full text |Cite
|
Sign up to set email alerts
|

The influence of microbiological fertilisers on the productivity and quality of winter wheat

Abstract: The study was aimed at assessing the yield and quality of winter wheat grains inoculated with Beijerinckia fluminensis (Azotovit) and Paenibacillus mucilaginosus (Phosphatovit) in a three-year experiment on leached Chernozem in the forest-steppe zone of the Middle Volga region. The seeds of the plants were treated before sowing with microbiological fertilisers, both individually and together at a dose of 2 L/t. Bacteria Beijerinckia fluminensis and Paenibacillus mucilaginosus contained in fertilisers increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Liu et al investigated the effects of complex microbial fertilizer on the growth conditions and soil nutrients of tomatoes, and the results showed that microbial fertilizer would substantially increase the root length, plant height, and leaf area of tomatoes [12]. Similarly, Koryagin has demonstrated that microbial fertilizers boost crop growth and yield [13]. However, the population and survival time of microorganisms in bio-fertilizers is still a huge challenge [14].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al investigated the effects of complex microbial fertilizer on the growth conditions and soil nutrients of tomatoes, and the results showed that microbial fertilizer would substantially increase the root length, plant height, and leaf area of tomatoes [12]. Similarly, Koryagin has demonstrated that microbial fertilizers boost crop growth and yield [13]. However, the population and survival time of microorganisms in bio-fertilizers is still a huge challenge [14].…”
Section: Introductionmentioning
confidence: 99%
“…Their versatility in any technological operation of agricultural crops cultivation is an advantage of these microbiological fertilizers and give a positive effect on any plant organism [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Bio-priming is a biological entitybased seed treatment that involves hydrating seeds and inoculating them with helpful microbes. This method the great majority of the studies have been performed are using seed inoculation with soaking the seeds (hardiansyah) before sowing with a suspension Beijerinckia fluminensis [15,16,17,18] or Rhizobium pusense [19,20,21]. In implanted pastures, there is also the limitation of inoculant application, another method would be via leaf-spray it is worth mentioning that there are positive indications of success of leaf-spray of A. brasilense in maize [22,23], encouraging to verify the feasibility on pastures but via leaf spray it will works on some spesific part such as the leaf.…”
Section: Introductionmentioning
confidence: 99%